Agreement Between County of Ventura and City of Oxnard Pertaining to Airport Development and Surrounding Area and Amendment #1 (1981)
The agreement between Ventura County and Oxnard discussing the rights each have in regards to the development of an airport in Oxnard, California. Includes an amendment which further clarifies these rights.